Design of high sensitive glucose concentration sensor of photonic crystal cavity. Issue 1 (February 2021) - Hocini, A; Mouetsi, S; Hocini, A; Saadoune, B
Abstract: Photonic sensors, in light of proposed structures comprised of rhombus–molded gaps matched with two waveguides, have been developed as another enthusiasm for specialists in science and technology. In this paper, it has been demonstrated that by utilizing the rhombus–formed openings examination, they got outcomes which are brilliant inside the depression locale. Consequently, the quality factor (Q) and the affectability (S) can be essentially improved for the proposed structure. This investigation are performed by reproduction utilizing limited contrast time area (FDTD). Different affectability are acquired as 494.15 nm/RIU and 445.75 nm/RIU and 482.84 nm/RIU and 483.63 nm/RIU and quality factor as high as 5739.5 and 1.17×10 4, 8.7×10 4 and 3489.9 have been accomplished, deducing in a location breaking points of 5.52×10 −5, 2.84×10 −5, 3.67×10 −6 and 9.14×10 −4 . This blend angle gives the proposed structure an extra exhibition as a component to play out a name free biosensing for the biomedical visualization.